Implementation of Sociopreneurs in Educational and Training Institutions in the Industrial Revolution Era 4.0 - Aidil Amin Effendy; Umi Narimawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the implementation of sociopreneurs in educational and training institutions in the era of the industrial revolution 4.0. This research method uses qualitative methods, with triangulation techniques in data collection, namely through observation, documentation and interviews with several informants from the Education and Training Institute. In interviews, this research uses the triangulation method between researchers, namely digging information from several different informants, including a sociopreneur from an educational and training institution, the participant or teacher and expert judgment who is an academic and sociopreneur practitioner who experienced. The results of the analysis from interviews, it was found that the Education and Training Institute had implemented sociopreneurs in their service sector, such as the Smart Muslim Education Institute which helps students who are pursuing a bachelor's degree education to be able to teach so that they earn income. Azkiya Qur'an Learning is also an Educational Institution that recruits teachers from the area or rural areas to teach Al-Qur'an Learning. As for the Training Institute, there is a TWT Learning Center that cares about education in Indonesia by providing community service in the form of free education and training at several universities and the surrounding community. Amal Insani Foundation organizes free webinars for lecturers, students and the general public, as well as the Billionaire School which has a business mentoring program that aims to produce young entrepreneurs in Indonesia so that they can compete in the era of the industrial revolution 4.0.